Voltammetric detection of Mn(II) in blood sample at C60 and MWCNT modified glassy carbon electrodes - Radhi, Muhammed Mizher (Science Publications, 2010)
Problem statement: Glassy carbon electrode GCE was modified with different microparticles to increase the efficiency of analysis Mn2+ in blood samples by cyclic voltammetry and applied for the detection of trace Mn(II) by oxidation process. Approach: The structure and composition of the modified GCE processed by using Carbon Nanotubes CNT and C60 to produce two modified electrodes CNT/GCE and C60/GCE, to detect a trace Mn2+ by cyclic voltammetry for mouse blood with comparison the best modified electrode for detection the ion by the sensitivity and values of Relative Standard Deviation (RSD) in calibration curve. Results: A wide linear range and good repeatability were obtained for Mn2+ detection by CNT/GCE in aqueous KCl as supporting electrolyte at different ratio of KCl: Blood using CNT/GCE and C60/GCE, the relative standard deviation of two modified electrodes are good on CNT/GCE than C60/GCE. Conclusion: The two modified electrodes CNT/GCE and C60/GCE depending on the redox current of Mn(II) ions were evaluated by the determination of low concentration of Mn(II) in blood samples by cyclic voltammetric method, the most modified electrode to detect the Mn(II) in blood is CNT/GCE.